The Influence of the Index Card Match Learning Model on Student Learning Motivation - Fadhli Dzil Ikrom; Nurul Hidayah, Siti Choirunnisa (LPPM Universitas Primagraha, 2022)
This study aims to determine the effect of the Index Card Match learning model on students' learning motivation. This research method uses a literature study, one of the studies is carried out by studying education studies, studies of educational books and journals. Based on the research, the result is that the Index Card Match learning model can increase students' learning motivation because Index Card Match is a fun learning model. The result of this study is that this study uses the literature study method, based on previous researchers who used research methods and classroom action research (CAR), stating that the Index Card Match learning model can affect students' learning motivation and have a positive influence on students